RADT-47. A MULTICENTER OBSERVATIONAL STUDY OF SURGICALLY TARGETED RADIATION THERAPY (START) USING IMPLANTED CS-131 SEEDS IN A COLLAGEN-BASED CARRIER TILE IN INTRACRANIAL BRAIN NEOPLASMS - PROTOCOL IN PROGRESS. (9th November 2020) - Nakaji, Peter; Brachman, David; Misell, Lisa
Abstract: INTRODUCTION: Post-resection radiotherapy (RT) is the most effective adjuvant treatment for brain tumors. However, there is no current consensus as to the "best" type of post-resection RT, either at diagnosis or recurrence. The use of internally placed radiation (brachytherapy) allows immediate initiation of RT when residual tumor burden is minimal, which theoretically should lessen the risk of recurrence. Brachytherapy placement intraoperatively allows more precise identification of the tumor margins than by postoperative imaging. Traditional brachytherapy methods have several drawbacks, including uneven dose distribution, long operating room times, a need for expensive equipment, and/or frequent adverse events (AE). To address these issues, a device with Cs-131 radiation seeds in a resorbable collagen-based carrier tile (GammaTile, GT Medical Technologies, Tempe AZ) was developed and is described as Surgically Targeted Radiation Therapy or STaRT. The device has demonstrated excellent safety and local control in early commercial use. OBJECTIVE: The objectives of this registry study are to evaluate real-world clinical outcomes and patient reported outcomes that measure the effectiveness and safety of STaRT. METHOD: Patients (N=600) with surgically resected (R) brain tumors of any pathology who have undergone STaRT are eligible. Accrual to start at 20+ sites in Q3 2020. Data collected includes local control, overall survival, QOL, neurocognition, functional decline, and surgical and radiation associated AE's. Data will be collected at 1, 3, 6, 9, and 12 months, then every 6 months through 5 years. RESULT: Data will be used to benchmark clinical outcomes of STaRT therapy and allow for comparisons to existing standard-of-care treatments. CONCLUSION: This will be the first observational registry study of R+STaRT, delivered by Cs-131 sources in permanently implanted resorbable collagen tile carriers. The outcome measures captured will allow for evaluation of the potential risks and benefits of this treatment approach for patients in a real-world setting.